Utilization of mobile learning in improving arabic vocabulary in elementary schools - Aisyah, Devy; Rezi , Melisa; Mudinillah, Adam; Ningsi, Putri Julia (Universitas Ahmad Dahlan, 2024)
Technological developments are indispensable in the world of education. Many schools are required to utilize mobile learning in the learning process. Educators can be more creative and innovative in using mobile learning to improve Arabic vocabulary at various levels, including elementary schools. This study aimed to determine the multiple benefits of mobile learning in improving Arabic vocabulary in elementary schools. This research method uses quantitative data from interviews and questionnaire dissemination. The questionnaire dissemination process is carried out online. The results showed that learning with mobile learning improves Arabic vocabulary in elementary schools. From the study, it can be concluded that mobile learning in improving Arabic vocabulary in elementary schools has proven effective and efficient. This is evidenced by the results of research that many elementary school students master increasing Arabic vocabulary. The limitation of this study is that researchers only research mobile learning, even though many other learning media can be used as alternatives in increasing Arabic vocabulary in elementary schools. Researchers hope that future researchers can conduct research related to increasing Arabic vocabulary by utilizing other learning media. This study also recommends further researchers to make research as a reference in improving Arabic vocabulary in elementary schools using mobile learning.